Lysosomal cystine accumulation promotes mitochondrial depolarization and induction of redox-sensitive genes in human kidney proximal tubular cells - Sumayao, R.; McEvoy, B.; Newsholme, Philip; McMorrow, T. (Wiley-Blackwell Publishing Ltd., 2016)
Key points: Cystine is a disulphide amino acid that is normally generated in the lysosomes by the breakdown of cystine-containing proteins. Previously, we demonstrated that lysosomal cystine accumulation in kidney proximal tubular epithelial cells (PTECs) dramatically reduced glutathione (GSH) levels, which may result in the disruption of cellular redox balance. In the present study, we show that lysosomal cystine accumulation following CTNS gene silencing in kidney PTECs resulted in elevated intracellular reactive oxygen species production, reduced antioxidant capacity, induction of redox-sensitive proteins, altered mitochondrial integrity and augmented cell death. These alterations may represent different facets of a unique cascade leading to tubular dysfunction initiated by lysosomal cystine accumulation and may present a clear disadvantage for cystinotic PTECs in vivo. Cystine depletion by cysteamine afforded cytoprotection in CTNS knockdown cells by reducing oxidative stress, normalizing intracellular GSH and ATP content, and preserving cell viability. Cystine is a disulphide amino acid that is normally generated within the lysosomes through lysosomal-based protein degradation and via extracellular uptake of free cystine. In the autosomal recessive disorder, cystinosis, a defect in the CTNS gene results in excessive lysosomal accumulation of cystine, with early kidney failure a hallmark of the disease. Previously, we demonstrated that silencing of the CTNS gene in kidney proximal tubular epithelial cells (PTECs) resulted in an increase in intracellular cystine concentration coupled with a dramatic reduction in the total GSH content. Because of the crucial role of GSH in maintaining the redox status and viability of kidney PTECs, we assessed the effects of CTNS knockdown-induced lysosomal cystine accumulation on intracellular reactive oxygen species (ROS) production, activity of classical redox-sensitive genes, mitochondrial integrity and cell viability. Our results showed that lysosomal cystine accumulation increased ROS production and solicitation to oxidative stress (OS). This was associated with the induction of classical redox-sensitive proteins, NF-?B, NRF2, HSP32 and HSP70. Cystine-loaded PTECs also displayed depolarized mitochondria, reduced ATP content and augmented apoptosis. Treatment of CTNS knockdown PTECs with the cystine-depleting agent cysteamine resulted in the normalization of OS index, increased GSH and ATP content, and preservation of cell viability. Taken together, the alterations observed in cystinotic cells may represent different facets of a cascade leading to tubular dysfunction and, in combination with cysteamine therapy, may offer a novel link for the attenuation of renal injury and preservation of functions of other organs affected in cystinosis.